UPAYA MENINGKATKAN MOTIVASI KERJA PADA KARYAWAN HOUSEKEEPING DEPARTMENT DI ASTON BATAM HOTEL & RESIDENCE - Togatorop, Josua Reza Fernando; Pristiwasa, I Wayan Thariqy Kawakibi; Fatimah, Zahara (Puslitabmas Batam Tourism Polytecnic, 2023)
This research will discuss efforts that can be taken by the management of Aston Batam Hotel & Residence to increase the work motivation of housekeeping staff in terms of quality and results. This research will involve identifying factors that influence housekeeping staff motivation, as well as developing strategies and policies that can increase their motivation. By understanding the dynamics of housekeeping motivation and work at Aston Batam Hotel & Residence, this research is expected to provide valuable insights for hotel management and the hospitality industry in general in their efforts to achieve higher service quality and maintain competitiveness in an increasingly competitive market. The research method used for this research is qualitative data and is described narratively. In this research, data collection techniques were used in the form of interviews, documentation, observation and triangulation. From the results of research at Aston Hotel & Residence, the author can draw the conclusion that the work motivation given to Room Attendant employees at Aston Hotel & Residence cannot be said to be optimal. Because there are still several things that must be considered, such as working environment conditions, effective communication, and physical working conditions